2022
DOI: 10.3390/polym14153020
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Azo Disperse Dyes with High Absorption for Efficient Polyethylene Terephthalate Dyeing Performances in Supercritical Carbon Dioxide

Abstract: Supercritical carbon dioxide dyeing (SCDD) not only enables strong dyeing performance for a versatile range of polymer material but is also regarded as a green chemical media due to its low environmental impact as well as low risk of product denaturation. Over the decades, azo disperse dyes have been revealed to be efficient dyes and represent the wide majority of dyeing material. Azo dyes possess a wide variety of functional groups to optimize dye synthesis and tune the light absorption properties. Using SCDD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…It is commonly admitted that the coupling process occurs under acidic conditions to increase the dye stability, as well as at a temperature of 0-5 • C to maintain the diazonium salt stability [3,38]. Furthermore, the choice of the functional group of the diazonium salt aromatic rings influence the rate of the coupling reaction in which a strong electron-withdrawing function will increase the coupling kinetics, resulting in decreased salt stability [3,13,27]. The dyes series 161 were obtained from previously obtained diazonium salt with the following 3-(N,N-diethyl)amino acetaniline coupling component.…”
Section: Dyes Synthesis and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…It is commonly admitted that the coupling process occurs under acidic conditions to increase the dye stability, as well as at a temperature of 0-5 • C to maintain the diazonium salt stability [3,38]. Furthermore, the choice of the functional group of the diazonium salt aromatic rings influence the rate of the coupling reaction in which a strong electron-withdrawing function will increase the coupling kinetics, resulting in decreased salt stability [3,13,27]. The dyes series 161 were obtained from previously obtained diazonium salt with the following 3-(N,N-diethyl)amino acetaniline coupling component.…”
Section: Dyes Synthesis and Characterizationmentioning
confidence: 99%
“…To overcome these drawbacks, replacing water by supercritical carbon dioxide as the dyeing media brings serious benefits. Supercritical carbon dioxide dyeing offers numerous advantages such as highly limited environmental impact, mitigated polymer swelling, low surface viscosity favoring dyeing agent penetration, and diffusion with limited by-product formation [5][6][7][8][9][10][11][12][13]. Furthermore, it has been demonstrated that dyeing under supercritical carbon dioxide environment suppresses product denaturation and promotes dye-stuff recovery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Green colorants cannot perfectly absorb blue light, and yellow additives should be added to a green colorant mixture to achieve high color purity of green [ 7 ]. Several dyes have been reported for yellow color, and a popular commercial yellow pigment is Y138 ( Scheme 1 ) [ 12 , 13 , 14 , 15 ]. The synthesized azo pyridone derivatives were studied to optimize their optical, thermal, and solvent stabilities depending on the chemical structures, and their potential as yellow color-filter materials was evaluated.…”
Section: Introductionmentioning
confidence: 99%